A green corrosion inhibitor and its preparation method and application
By preparing green corrosion inhibitors with specific structures, the problems of unstable performance and high cost of existing corrosion inhibitors are solved, and efficient corrosion inhibition effects and environmentally friendly corrosion inhibitor industrialization are achieved.
Patent Information
- Application Number
- CN202411685349.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-08
Smart Images

Figure CN119776848A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal pickling corrosion and protection, and specifically relates to a green corrosion inhibitor and a preparation method and application thereof. Background Art
[0002] Among many metal materials, Q235 steel has good strength and toughness, and is easy to cast and weld, so it is widely used in construction, transportation, ocean and other fields. However, Q235 steel is very prone to corrosion in industrial applications, especially in the process of metal pickling, oil well acidification, descaling and other fields. Seemingly insignificant corrosion has a great impact on social security, economic development, ecological environment and other fields. At present, corrosion inhibitors are one of the most efficient and economical ways to slow down the corrosion of metals and alloys.
[0003] In the past few decades, organic corrosion inhibitors have developed rapidly due to their high corrosion inhibition efficiency, but these corrosion inhibitors are usually highly toxic and easy to cause environmental pollution. In the context of green development, corrosion inhibitors are developing in the direction of low phosphorus, phosphorus-free, and heavy metal-free. Currently common green corrosion inhibitors include some plant extracts, biopolymers, surfactants, and ionic liquids. These corrosion inhibitors can form an adsorption layer by physically or chemically reacting with the metal surface, thereby effectively preventing or reducing the contact between the metal surface and the corrosive ions in the solution and reducing its corrosion rate. However, these green corrosion inhibitors have problems such as unstable performance and low corrosion inhibition rate. In addition, plant extracts, ionic liquids, and biopolymers are difficult to obtain, costly, and may produce environmental waste.
[0004] Amino acids have become a green corrosion inhibitor with great development potential due to their slow release, water solubility, easy degradation, wide sources and easy purification. In recent years, the research on amino acids as metal corrosion inhibitors has gradually increased.
[0005] Existing green corrosion inhibitors have problems such as unstable performance and low corrosion inhibition rate. In addition, plant extracts, ionic liquids and biopolymers are difficult to obtain, costly and may produce environmental waste.
[0006] Like most green corrosion inhibitors, the inhibition rate of amino acid molecules is not high in many corrosive environments due to the small number of electron donors in the amino acid molecules. Studies have found that introducing suitable groups into amino acid molecules through various means can provide new adsorption sites to improve their inhibition rate. However, the modification of amino acids can only improve their inhibition efficiency to a certain extent, and the synthesis of such amino acid corrosion inhibitors is difficult and the synthesis efficiency is low, so it cannot be industrialized. In addition, the environmental friendliness of the monomers used to modify amino acids is also an important issue that needs to be considered. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a green corrosion inhibitor.
[0010] In order to solve the above technical problems, the present invention provides the following technical solution, a green corrosion inhibitor, wherein the chemical structural formula of the green corrosion inhibitor is as shown in formula (I):
[0011]
[0012] Wherein, the R group is one of formula (II) and formula (III),
[0013]
[0014] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a green corrosion inhibitor.
[0015] As a preferred embodiment of the preparation method of the present invention, the method comprises:
[0016] Nicotinic acid, amino acid methyl ester hydrochloride, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDCI and N-methylmorpholine are mixed and reacted in a solvent to obtain an intermediate product, wherein the chemical structural formula of the intermediate product is shown in (IV);
[0017] After the intermediate product is dissolved, LiOH is added thereto, and a green corrosion inhibitor is obtained after reaction and acidification;
[0018]
[0019] As a preferred embodiment of the preparation method of the present invention, the amino acid methyl ester hydrochloride is one of phenylalanine methyl ester hydrochloride and tryptophan methyl ester hydrochloride.
[0020] As a preferred embodiment of the preparation method of the present invention, the volume ratio of nicotinic acid: amino acid methyl ester hydrochloride: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDCI: N-methylmorpholine is 1:1-2:2-3:3-4.
[0021] As a preferred embodiment of the preparation method of the present invention, the solvent is dichloromethane.
[0022] As a preferred embodiment of the preparation method of the present invention, the amino acid methyl ester hydrochloride, nicotinic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) and N-methylmorpholine are mixed in a solvent and stirred at 20-25° C. for 10-14 hours.
[0023] As a preferred embodiment of the preparation method of the present invention, the reaction conditions after adding LiOH are stirring at 20-25° C. for 1-3 hours.
[0024] As a preferred embodiment of the preparation method of the present invention, 1-2M HCl is used for acidification.
[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide a green corrosion inhibitor for use in slowing down the corrosion of metals and alloys.
[0026] As a preferred solution of the application of the present invention, the metal is low carbon steel.
[0027] Beneficial effects of the present invention:
[0028] 1. The present invention modifies amino acids by nicotinic acid to obtain a green corrosion inhibitor having a structure as shown in formula (I). Tests show that the green corrosion inhibitor exhibits excellent corrosion inhibition ability and has a high corrosion inhibition efficiency;
[0029] 2. The present invention uses amino acid methyl ester hydrochloride and nicotinic acid as raw materials to prepare a green corrosion inhibitor. The raw materials are all necessary for the human body, are environmentally friendly, and will not cause environmental pollution. In addition, the raw materials of the preparation method are simple and easy to obtain, the synthesis conditions are simple, the synthesis efficiency is high, and industrialization can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0031] Figure 1 These are the hydrogen spectrum and mass spectrum of the green corrosion inhibitor HPA in Example 1 of the present invention, wherein a is the hydrogen spectrum of the green corrosion inhibitor HPA, and b is the mass spectrum of the green corrosion inhibitor HPA.
[0032] Figure 2These are the hydrogen spectrum and mass spectrum of the green corrosion inhibitor PPA in Example 2 of the present invention, wherein a is the hydrogen spectrum of the green corrosion inhibitor PPA, and b is the mass spectrum of the green corrosion inhibitor PPA.
[0033] Figure 3 Surface SEM images of Q235 carbon steel in the embodiment of the present invention, wherein a is a surface SEM image of Q235 carbon steel in 1M HCl solution in Example 2 of the present invention; b is a surface SEM image of Q235 carbon steel in 1M HCl solution containing 200 mg / L PPA in Example 2 of the present invention; c is a surface SEM image of Q235 carbon steel in 1M HCl solution containing 200 mg / L HPA in Example 2 of the present invention; d is a high-magnification SEM image of Q235 carbon steel in 1M HCl solution in Example 2 of the present invention; e is a high-magnification SEM image of Q235 carbon steel in 1M HCl solution containing 200 mg / L PPA in Example 2 of the present invention; f is a high-magnification SEM image of Q235 carbon steel in 1M HCl solution containing 200 mg / L HPA in Example 2 of the present invention; g is an SDM image of Q235 carbon steel in 1M HCl solution in Example 2 of the present invention; h is a high-magnification SEM image of 1M HCl solution containing 200 mg / L PPA in Example 2 of the present invention; SDM diagram of Q235 carbon steel in HCl solution; i) is the SDM diagram of Q235 carbon steel in 1M HCl solution containing 200 mg / L HPA in Example 2 of the present invention.
[0034] Figure 4 Surface XPS high-resolution spectrum of carbon steel in 1M HCl solution containing 200 mg / L PPA or HPA in an embodiment of the present invention, wherein a is the overall spectrum; b is Fe 2p; c is C1s; d is O1s; and e is N1s.
[0035] Figure 5 The dipole moment and ESP distribution diagram of the PPA and HPA after the geometric structure optimization in the embodiment of the present invention.
[0036] Figure 6 Graph showing the distribution of frontier molecular orbitals and related parameter calculation values for PPA and HPA in the embodiments of the present invention. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention, so the present invention is not limited to the specific embodiments disclosed below. Secondly, the "one embodiment" or "embodiment" referred to herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not all refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0039] The raw materials and reagents used in the present invention: tryptophan methyl ester hydrochloride (98%), nicotinic acid (PI, 97%), LiOH (AR, 98%), methanol (AR, 98%) and THF (AR, 98%) were purchased from Aladdin. EDCI (AR, 99%) and N-methylmorpholine (AR, 99%) were purchased from MacLean.
[0040] The test material used in the experiment is Q235 steel, whose element composition (wt%) is as follows: 0.062% C, 0.326% Mn, 0.009% P, 0.013% S, and the rest is Fe. The sample size is 1×1×0.5cm3. Before the test, the sample is polished with 400#, 800#, 1200#, 1500# and 2000# sandpaper in turn. When conducting the electrochemical test, a copper wire is welded on the back of each sample as a conductor and sealed with epoxy resin. The exposed area of the sample is 1cm 2 , the corrosion medium is 1M HCl solution.
[0041] Example 1 Synthesis of Green Corrosion Inhibitor HPA
[0042] First, 1 mol of nicotinic acid, 1.1 mol of tryptophan methyl ester hydrochloride, 2 mol of EDCI, and 3 mol of N-methylmorpholine (NMM) were added into a flask containing dichloromethane and stirred at room temperature for 12 h;
[0043] Dilute with dichloromethane, wash with water and brine, dry, filter and concentrate under reduced pressure, and purify by column chromatography (dichloromethane: petroleum ether = 1:1) to obtain ester (intermediate product);
[0044] Add 5 mol of LiOH to a solution of 1 mol of ester (intermediate product) dissolved in methanol and THF, and stir at room temperature for 2 h;
[0045] The solvent was evaporated, diluted with water, acidified with 1.5M HCl, extracted with ethyl acetate, dried and concentrated to obtain the target product HPA. The chemical structure of HPA is as shown in Formula (V).
[0046]
[0047] Hydrogen spectrum and mass spectrometry characterization of HPA Figure 1 As shown, the yield is: 80%.
[0048] 1 H NMR (400 MHz, MeOD): δ H 8.88-8.78(m,1H),8.70-8.58(m,1H),8.18-8.06(m,1H),7.59(d,J=7.9Hz,1H),7.49(dd,J=8.0,4.9Hz,1H),7.32(d,J=8.1H z,1H),7.14(s,1H),7.07(t,J=7.5Hz,1H),6.98(t,J=7.4Hz,1H),4.95(dd,J=8.7,4.9Hz,1H),3.51(dd,J=14.8,4.9Hz,1H);
[0049] HRMS: (ESI + )calculated for C 17 H 15 N3O3[M+H] + :310.1186, found 310.1183.
[0050] Example 2 Synthesis of green corrosion inhibitor PPA
[0051] 1 mol of nicotinic acid, 1.1 mol of phenylalanine methyl ester hydrochloride, 2 mol of EDCI, and 3 mol of N-methylmorpholine (NMM) were added to a flask containing dichloromethane and stirred at room temperature for 12 h;
[0052] Dilute with dichloromethane, wash with water and brine, dry, filter and concentrate under reduced pressure, and purify by column chromatography (dichloromethane: petroleum ether = 1:1) to obtain ester (intermediate product);
[0053] Add 5 mol of LiOH to a solution of 1 mol of ester (intermediate product) dissolved in methanol and THF, and stir at room temperature for 2 h;
[0054] The solvent was evaporated, diluted with water, acidified with 1.5M HCl, extracted with ethyl acetate, dried and concentrated to obtain the target product PPA. The chemical structure of PPA is as shown in Formula (VI):
[0055]
[0056] The hydrogen spectrum and mass spectrometry characterization of PPA are shown in Figure 2 As shown. The yield is: 74%.
[0057] 1H NMR (400 MHz, MeOD): δ H 8.84(s,1H),8.65(d,J=5.0Hz,1H),8.13(d,J=7.9Hz,1H),7.51(dd,J=8.0,4.9Hz,1H),7.27(d ,J=5.4Hz,4H),7.23–7.14(m,1H),3.37(dd,J=14.0,4.9Hz,1H),3.10(dd,J=14.0,4.9Hz,1H);
[0058] HRMS:(ESI + )calculated for C 15 H 14 N2O3[M+H] + :271.1077,found 271.1075.
[0059] The fitting parameters of the polarization curves of carbon steel in 1 M HCl solutions without or with different concentrations of PPA or HPA are shown in Table 1.
[0060] Table 1
[0061]
[0062]
[0063] After a 30-minute open circuit potential (OCP) test, the polarization curve was measured at a scan rate of 0.5 mV / s in a potential range of (E0-250 mV) to (E0+250 mV). The corrosion potential (Ecorr), corrosion current density (icorr) and cathode Tafel slope (bc) were obtained by analyzing the polarization curve.
[0064] Formula 4 calculates the corrosion inhibition rate (P%) of the corrosion inhibitor
[0065]
[0066] In the formula, i 0 corr and icorr are the corrosion current densities of Q235 measured in the blank control solution and the solution with corrosion inhibitor, respectively.
[0067] Compared with the blank control, the corrosion potential of carbon steel did not change by more than 85 mV after adding PPA or HPA, indicating that both PPA and HPA are mixed corrosion inhibitors. In addition, the corrosion current density on the carbon steel surface was significantly reduced after adding the corrosion inhibitor, indicating that these two molecules can form a barrier film on the carbon steel surface and effectively inhibit its corrosion in HCl medium.
[0068] The electrochemical parameters obtained by fitting the polarization curves and the corresponding corrosion inhibition efficiencies are listed in Table 1. As can be seen from the table, the corrosion current density of the sample in the blank solution (2.08×10 –3 A / cm 2 ) is significantly higher than the corrosion current density at different PPA and HPA concentrations, indicating that the sample suffered severe corrosion in the blank solution. With the increase of PPA and HPA concentrations, the corrosion current density of the sample decreased, and the corrosion inhibition efficiency of the corrosion inhibitor increased. After adding 200 mg / L of PPA and HPA, the corrosion current density increased from 2.08×10 –3 A / cm 2 It dropped sharply to 3.07×10 –4 A / cm 2 and 7.07×10 –5 A / cm 2 , the corresponding corrosion inhibition rates reached 85.24% and 96.61%.
[0069] Example 3
[0070] At 25°C, the samples were immersed in blank or inhibitor-containing test solutions for 24 hours. The samples were taken out and rinsed with deionized water and dried. The surfaces of the samples were then characterized using scanning electron microscopy (SEM), ultra-depth microscopy, and X-ray photoelectron spectroscopy (XPS) to analyze the corrosion morphology, surface composition, and roughness of the samples.
[0071] Figure 3 a~c are SEM morphology images of Q235 samples after being immersed in 1M HCl solution without or containing 200 mg / L PPA or HPA for 24 hours. In the absence of corrosion inhibitor, carbon steel is in direct contact with the acid and there are a large number of corrosion products on the surface; after adding 200 mg / L PPA, the surface products are relatively reduced, and after adding 200 mg / L HPA, the surface products of the sample are further reduced.
[0072] From the SEM local enlarged image ( Figure 3 d~f), it can be found that the corrosion products on the carbon steel surface are lamellar pearlite and residual nitride after corrosion, which directly proves the excellent corrosion inhibition performance of PPA and HPA on Q235 steel in 1M HCl solution.
[0073] Figure 3 g~i are relative images of carbon steel under ultra-depth microscope. It can be seen that the addition of PPA and HPA can effectively delay the corrosion of carbon steel in acid solution and keep its surface smooth and uniform.
[0074] From the XPS high-resolution spectrum ( Figure 4) It can be seen that after the carbon steel was immersed in the test solution containing 200 mg / L PPA or HPA for 24 hours, the surface of the sample contained four elements, Fe, C, O and N. The presence of C and N elements proves the adsorption of PPA or HPA molecules on the surface of the sample. For the Fe 2p spectrum, the peaks at 731.5eV, 724.8eV, 717.7eV, 712.8eV, and 710.8eV come from FeO, Fe3O2, FeO, FeOOH, and Fe3O2. The C 1s spectrum has three peaks at 288.3eV, 285.6eV, and 284.6eV, which are respectively attributed to CN, CC / C=O, and C=C / CH. The O1s spectrum has three peaks at 531.6eV, 531.0eV, and 529.8eV, which are respectively attributed to OH in the test solution. - , the C=O fragment in the corrosion inhibitor molecule and the O 2- For the N1s spectrum, the peaks at 400.8eV, 399.8eV, and 399.0eV are charged nitrogen (=N+-), CN-Fe, and CN, respectively. These results indicate that PPA and HPA can be adsorbed on the surface of Q235 steel.
[0075] Example 4
[0076] Based on density functional theory (DFT), quantum chemical calculations of PPA and HPA were performed using Gaussian 09 at the B3LYP / 6-311G* level to obtain the geometrically optimized structure and frontier orbital (HOMO, LUMO) distribution. At the same time, their dipole moment and electrostatic potential (ESP) distribution were analyzed to explore the possible adsorption sites and strengths of PPA and HPA. After the calculations were completed, Multiwfn and VMD were used to post-process the data and visualize the optimized structure.
[0077] Figure 5 The direction and magnitude of the dipole moment of the PPA and HPA molecules after geometric structure optimization and the distribution of electrostatic potential (ESP) on the van der Waals (vdW) surface are shown. The physical adsorption capacity of the corrosion inhibitor molecules is positively correlated with the dipole moment (μ) value. The dipole moment μ of PPA is 4.57 Debye and that of HPA is 3.65 Debye. The ESP isosurface map can predict the possible adsorption sites of the corrosion inhibitor molecules on the metal surface, among which the nucleophilic active sites are mainly located in the blue area. It can be observed from the figure that the ESP on the vdW surface around heteroatoms and heterocycles is more negative than other areas, indicating that these areas may be the nucleophilic reaction sites of PPA and HPA. In addition, the similarity of the ESP maximum and minimum values of PPA and HPA molecules indicates that they have similar electrostatic properties.
[0078] Figure 6The highest occupied molecular orbital (HOMO) and lowest occupied molecular orbital (LUMO) of PPA and HPA molecules are shown. In PPA molecules, the HOMO orbital is mainly distributed on the carbon chain of the benzene ring and its vicinity, and a small amount is also distributed around the amide group; the LUMO orbital is mainly distributed near the pyridyl and amide groups; in contrast, the HOMO orbital of the HPA molecule is mainly distributed on the carbon chain of the indole group and its vicinity, while the LUMO orbital is distributed near the pyridyl and amide groups. According to the frontier molecular orbital theory, these orbitals can represent the reactivity of the molecule, usually E HOMO The value of is positively correlated with the electron-donating ability of the molecule. Compared with PPA (-6.818 eV), HPA's E HOMO (-5.784eV) is higher, that is, HPA has stronger electron-donating ability; E LOMO The value of E is positively correlated with the strength of the molecule's electron-accepting ability. Compared with HPA (-1.736 eV), PPA's E LUMO (-1.792eV) is lower, that is, PPA has a stronger ability to obtain electrons. The Fermi level of iron is -5.177eV, so electrons can be transferred between the corrosion inhibitor and Fe.
[0079] In addition, the value of the energy gap (ΔE) is positively correlated with the molecular stability, and the ΔE of HPA (4.048 eV) is lower than that of PPA (5.026 eV). These results indicate that HPA can undergo more electron transfer with the Fe surface.
[0080] Comparative Example 1
[0081] The corrosion inhibitor L-Tryptophanate methyl ester hydrochloride (TMEH) was selected.
[0082] Comparative Example 2
[0083] The corrosion inhibitor L-Phenylalanine methyl ester hydrochloride (PMEH) was selected.
[0084] Comparative Example 3
[0085] The corrosion inhibitor Nicotinic acid (NA) is selected.
[0086] The fitting parameters of the polarization curves of carbon steel in 1 M HCl solutions without or with 100 mg / L TMEH, PMEH or NA are shown in Table 2.
[0087] Table 2
[0088]
[0089]
[0090] As shown in Table 2, when 100 mg / L of raw materials PMEH, TMEH and NA were added, the corrosion current density of carbon steel increased from 1.33×10 –3 A / cm 2 Down to 7.80×10 –4 A / cm 2 8.20×10 –4 A / cm 2 and 4.80×10 –5 A / cm 2 , the corresponding corrosion inhibition rates reached 41.35%, 38.35% and 63.91%, which were lower than those of HPA (90.91%) and PPA (79.33%) synthesized at the same concentration in Table 1.
[0091] Comparative Example 4
[0092] The corrosion inhibitor tryptophan derivative 5-hydroxy-L-tryptophan (HTrp) was selected.
[0093] Comparative Example 5
[0094] The corrosion inhibitor tryptophan benzimidazole derivative 1-(1H-benzo[d]imidazol-2-yl)-2-(1H-indol-3-yl)ethan-1-amine (BIT) was selected.
[0095] The fitting parameters of the polarization curves of carbon steel in 1 M HCl solution without or with 200 mg / L HTrp or BIT are shown in Table 3.
[0096] Table 3
[0097]
[0098] As shown in Table 3, when 200 mg / L of tryptophan derivatives (Comparative Example 4) were added, the corrosion current density of carbon steel increased from 3.21×10 –4 A / cm 2 Down to 4.30×10 –5 A / cm 2 , the corresponding corrosion inhibition rate reached 86.60%; when 200 mg / L of tryptophan derivatives (Comparative Example 5) were added, the corrosion current density of carbon steel increased from 6.326×10 –4 A / cm 2 Down to 1.236×10 –4 A / cm 2, the corresponding corrosion inhibition rate reaches 80.46%; the corrosion inhibition rate is lower than that of the corrosion inhibitor HPA (96.61%) synthesized at the same concentration in Table 1.
[0099] Comparative Example 6
[0100] The corrosion inhibitor amino acid thiophenecarboxamide derivative (thiophene-3-carbonyl) methionine (TOP-Meth) was selected.
[0101] The fitting parameters of the polarization curves of carbon steel in 1 M HCl solutions without or with different concentrations of TOP are shown in Table 4.
[0102] Table 4
[0103]
[0104] As shown in Table 4, when different concentrations of amino acid amide corrosion inhibitors were added, the corrosion current density of carbon steel increased from 7.465×10 –2 A / cm 2 Down to 3.203×10 –2 A / cm 2 , 2.597×10 –2 A / cm 2 , 2.242×10 –2 A / cm 2 and 2.045×10 –2 A / cm 2 The corresponding corrosion inhibition rates are 63.15%, 68.34%, 72.67% and 75.07%, which are lower than those of the corrosion inhibitors synthesized at the same concentration in Table 1.
[0105] Comparative Example 7
[0106] The fitting parameters of the polarization curves of carbon steel at different temperatures in 1 M HCl solution without or with 200 mg / L PPA or HPA are shown in Table 5.
[0107] Table 5
[0108]
[0109]
[0110] Table 5 shows the polarization curve parameters of carbon steel in blank solution or 1M HCl solution with 200 mg / L corrosion inhibitors PPA and HPA added in the range of 25-40°C. As the temperature decreases, the polarization current density of carbon steel decreases, the corrosion rate decreases, and the corrosion inhibition rate of amino acid derivatives on carbon steel increases with the decrease in temperature. At different temperatures, the corrosion inhibition rate of corrosion inhibitor HPA is more excellent.
[0111] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A green corrosion inhibitor, characterized in that: The chemical structural formula of the green corrosion inhibitor is shown in formula (I): Wherein, the R group is one of formula (II) and formula (III), 2. A method for preparing a green corrosion inhibitor, characterized in that: include, Nicotinic acid, amino acid methyl ester hydrochloride, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDCI and N-methylmorpholine are mixed and reacted in a solvent to obtain an intermediate product, wherein the chemical structural formula of the intermediate product is shown in (IV); After the intermediate product is dissolved, LiOH is added thereto, and a green corrosion inhibitor is obtained after reaction and acidification; 3. The preparation method according to claim 2, characterized in that: The amino acid methyl ester hydrochloride is one of phenylalanine methyl ester hydrochloride and tryptophan methyl ester hydrochloride.
4. The preparation method according to claim 2, characterized in that: In terms of volume ratio, the nicotinic acid: amino acid methyl ester hydrochloride: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDCI: N-methylmorpholine is 1:1-2:2-3:3-4.
5. The preparation method according to claim 2, characterized in that: The solvent is dichloromethane.
6. The preparation method according to claim 2, characterized in that: The amino acid methyl ester hydrochloride, nicotinic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) and N-methylmorpholine are mixed in a solvent and stirred at 20-25° C. for 10-14 hours.
7. The preparation method according to claim 2, characterized in that: The reaction condition after adding LiOH is stirring at 20-25° C. for 1-3 hours.
8. The preparation method according to claim 2, characterized in that: Acidification was performed using 1-2 M HCl.
9. Use of the green corrosion inhibitor prepared by the preparation method according to any one of claims 2 to 8 in slowing down metal corrosion in inorganic pickling media.
10. The use according to claim 9, characterized in that: The metal is low carbon steel.